Magnetostrictive Vibration Model for Evaluation of Mechanical Integrity of Power Transformer Magnetic Core - Marks J. (Latvian Journal of Physics and Technical Sciences, 2019)
Magnetostriction process creates vibrations within magnetic core of a power transformer. This effect can cause delamination of magnetic core layers and increase the vibration amplitudes on the surface of transformer tank. In this paper, a magnetostrictive vibration model is proposed for improved evaluation of the mechanical integrity of magnetic core and the finding of possible mechanical defects. This model is based on the simulation of magnetostrictive vibrations by replacing the magnetic core with mass and spring system, and application of a dynamic genetic algorithm in order to find the necessary system configuration. A case study is provided structurally modelling magnetic core in Matlab and Matlab Simulink with the analysis of simulated vibrations that indicate a possible mechanical defect.